Experiences of New Nurses in Dealing with Patient Safety Incidents During the Orientation Period in the Inpatient Room - Nur, Muh. Fadli; Susilaningsih, F. Sri; Setiawati, Setiawati (Indonesian Journal of Global Health Research, 2024)
This research aims to explore in depth about the experiences of new nurses in the inpatient room which emphasizes the importance of a positive work environment in quality patient care. This research used a qualitative method with a phenomenological approach and was conducted at the Kiwari Bandung Regional Hospital, Bandung City, with a total of 10 participants, including 7 new nurses and 3 in charge of shifts. This research focuses on the experience of new nurses in dealing with patient safety incidents during the orientation period in the inpatient room with data analysis techniques carried out using the Colaizzi method, namely the researcher's ability to read, intuit, analyze, describe, and report findings.. It is concluded that this research can provide an in-depth understanding of the experiences of new nurses who face patient safety incidents during the orientation period in the inpatient room. In addition, this research provides an understanding of the challenges and adaptation strategies of new nurses in handling patient safety events for orientation. Practical implications of this research include the development of more depth-oriented programs, increased social support, and more effective integration of patient safety policies into daily clinical practice. Thus, new nurses experience significant emotional distress and anxiety when faced with patient safety events. Social support and interpersonal relationships, particularly from mentors, play an important role in helping them overcome emotional burdens. Personal reflection and attention to mental well-being become important strategies for recovery.